The Determinants of Location Choice: Single-Plant Versus Multi-Plant Firms - Isabel Mota; Antonio Brandao (European Regional Science Association (ERSA), 2006)
In this paper, we intend to evaluate the importance of geographical and technological variables for firms' decision about location. For that purpose, we make use of micro-level data for the Portuguese manufacturing sector and focus on the location choices made by new starting plants during 1992-2000 within 275 municipalities. Our main hypothesis is that location determinants affect unevenly single-plant and multi-plant firms. We then considered the entire manufacturing sector and also a partition according to the number of plants. The set of explanatory variables includes variables that are traditionally stressed by urban and regional theory, such as production costs (land, labour and capital costs), demand variables and agglomeration economies as well as technological variables, such as R&D expenditures The model is based on the random utility maximization framework and proceeds through a Poisson model and a Negative Binomial regression. When considering the total manufacturing sector, our results confirm the relevance of agglomeration economies (particularly, urbanization economies) and cost factors (labour and land costs) for firms' location choice. On the contrary, the hypothesis concerning the negative influence of capital costs on location choice is not confirmed in our study. Our research also evidences that the regional market is more significant for the location choice of new single plant firms, while the local market is more relevant for new multi-plant firms. Also, market accessibility is only relevant for the location choices made by new single-plant firms. We then concluded that new multi-plant firms are particularly sensitive to urbanization economies, land costs and local market, while new single-plant firms are more responsive to labour costs and agglomeration economies.
Keywords: 330